Should Trade Remedies be Eliminated from WTO: A Response to Tania Voon - Utkarsh K. Mishra; Abhishek Negi (Journal of Human Rights, Culture and Legal System, 2021)
This work is a reflection of a critical viewpoint on the academic work of Tania Voon. She argues on the elimination of trade remedies from the multilateral trading system of the World Trade Organization on the basis of various considerations, including on the basis of some lessons from Regional Trade Agreements. The article makes no attempt to strike a balance between consumer and domestic industry interests. Additionally, it must be recognized that eliminating a structural protection mechanism is not always the best course of action because, in a global market such as that of trade, there are numerous players with disparate interests. If trade remedies are eliminated, a void will exist in which there will be nothing to regulate short-term issues, which will also affect the WTO's long-term objectives.